Analisis Audit Sistem Informasi Pada Pengaruh Pelayanan Nasabah di BPJS Ketenagakerjaan: (Studi Kasus BPJS Ketenagakerjaan Binjai) - Ikhsan Arif; Prisa Abela; Nurul Syahrani; Dina Ervianna Simarmata (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Information system audits have an important role in ensuring the quality of customer service at BPJS Ketenagakerjaan. This study aims to analyze the effect of information system audits on customer service at BPJS Ketenagakerjaan, with a case study focus on the Binjai branch office. The background of this research is the important role of information systems in supporting BPJS Ketenagakerjaan operations and services. Along with technological developments, the reliability, security and efficiency of information systems are crucial in maintaining the quality of service to customers. Therefore, an information system audit is needed to ensure that the system runs according to predetermined standards and is able to provide the best service.